Highlights of the 2014 Guidelines for Asymptomatic PHPT - Mosley, Mary (MD Conference Express, 2014)
Primary Hyperparathyroidism (PHPT) is a common disorder, and surgery is a curative option for patients whose PHPT is symptomatic, unless there is a contraindication. The Guidelines for the Management of Asymptomatic PHPT are reviewed in this article.